Unfolding Stories of Undergraduate Thesis Writers: Voices from EFL learners at Islamic Higher Education - Khasanah, Rima; Ningrum, Ary Setya Budhi; Toyyibah, Toyyibah; Umam, Chothibul (Makassar State University, 2023)
Abstract. This study aimed to investigate the challenges and strategies faced by undergraduate students in Islamic Higher Education when writing theses. The study had four participants, two of whom completed their degrees on time (SGO) and two who failed to do so (SGN). Despite both groups facing challenges and employing strategies, they had some differences in their experiences. Common issues faced by both groups were difficulty generating ideas, selecting a topic, feeling confused and anxious, and procrastination due to various reasons. SGN students faced additional problems such as laziness, unexpected events, and issues with supervisors. The study also found that family support and spiritual practices like prayers and invocations helped students complete their theses. The support and encouragement from their parents served as a significant boost to the students' motivation in finishing the thesis. The study highlights the importance of surrendering to Allah's plan and trusting His wisdom, as well as maintaining a positive outlook and seeking support from family and spirituality. Overall, the study uncovered various problems faced by undergraduate students and the strategies they used to deal with them, emphasizing the importance of perseverance and relying on Allah's guidance.Keywords: Thesis Writing, Challenges, Strategies, Islamic Higher Education, Narrative Inquiry